1981
DOI: 10.1073/pnas.78.3.1967
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal secretory, motor, circulatory, and metabolic effects of prosomatostatin.

Abstract: This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Preprosomatostatins are polypeptides of 120 or more amino acids and usually contain the somatostatin-28 sequence at the C-terminus. 4 5 When infused in pharmacological doses into animals or man somatostatin-14 inhibits many endocrine and gastrointestinal functions.6 Somatostatin-28 is also a pharmacological inhibitor although it can differ from somatostatin-14 in specific effects.7 8 Four interrelated functions have been proposed for endogenous somatostatin: (a) neurohumeral regulator, (2) neurotransmitter (3) endocrine hormone and (4) paracrine hormone. There is strong evidence that I I H2 -N-Ala-Gly-Cys-Lys-Asn-Phe-Phe-Trp-Lys-Thr-Phe-Thr-Ser-Cys-COOH 1 2 3 4 5 6 7 8 9 10 11 12 13 14 Somatostatin-1L Ala-G ly-Cys-Lys-Asn-Phe-Phe-Trp-Lys-Thr-Phe-Thr-Ser-Cys-COO H 15 16 17 18 19 20 21 22 23 24 25 26 27 28 Somatostatin-28 endogenous somatostatin is a neurohumeral regulator of secretion by the anterior pituitary gland of growth hormone and probably thyroid stimulating hormone9; and that somatostatin acts as a peptidergic neurotransmitter in autonomic nerves."'…”
Section: Endogenous Somatostatin and The Gutmentioning
confidence: 99%
“…Preprosomatostatins are polypeptides of 120 or more amino acids and usually contain the somatostatin-28 sequence at the C-terminus. 4 5 When infused in pharmacological doses into animals or man somatostatin-14 inhibits many endocrine and gastrointestinal functions.6 Somatostatin-28 is also a pharmacological inhibitor although it can differ from somatostatin-14 in specific effects.7 8 Four interrelated functions have been proposed for endogenous somatostatin: (a) neurohumeral regulator, (2) neurotransmitter (3) endocrine hormone and (4) paracrine hormone. There is strong evidence that I I H2 -N-Ala-Gly-Cys-Lys-Asn-Phe-Phe-Trp-Lys-Thr-Phe-Thr-Ser-Cys-COOH 1 2 3 4 5 6 7 8 9 10 11 12 13 14 Somatostatin-1L Ala-G ly-Cys-Lys-Asn-Phe-Phe-Trp-Lys-Thr-Phe-Thr-Ser-Cys-COO H 15 16 17 18 19 20 21 22 23 24 25 26 27 28 Somatostatin-28 endogenous somatostatin is a neurohumeral regulator of secretion by the anterior pituitary gland of growth hormone and probably thyroid stimulating hormone9; and that somatostatin acts as a peptidergic neurotransmitter in autonomic nerves."'…”
Section: Endogenous Somatostatin and The Gutmentioning
confidence: 99%
“…At least five different endocrine cell types have been recognized in the pancreas which elaborate polypeptides and amines (serotonin), and an occasional overproduction of some hormones by tumors, causing syndromes, would not be unexpected. These actions include inhibition of the release of insulin and glucagon from the pancreas and suppression of the secretion and/or action of gastrin, secretin, cholecystokinin (CCK), and VIP (4,154,155). Entopic endocrine tumors include insulinomas, glucagonomas, somatostatinomas, and pancreatic polypeptide (PP) islet cell tumors (PPomas, PP apudomas) ( 154).…”
Section: Chondrosarcomas and Osteosarcomas Or Tumors Of Cartilage Andmentioning
confidence: 99%
“…Somatostatin analogs reduce the growth of pancreatic ductal and acinar cancers, probably by inhibiting the release and/or stimulatory action of gastrointestinal hormones on tumor cells ( 155,178). In Wistar-Lewis rats bearing the acinar pancreatic tumors DNCP-322, chronic administration of L-5Br-Trp-8-S-S, a powerful analog of somatostatin-14, significantly decreased tumor weights and volume.…”
Section: Chondrosarcomas and Osteosarcomas Or Tumors Of Cartilage Andmentioning
confidence: 99%
“…In rats (Meyers et al 1980;Brown et al 1981) SS-28 has been reported to be more effective than SS-14. In contrast, in dogs (Vaysse et al 1981a;Konturek et al 1981) the peptides are reported to have a similar effect in suppressing insulin secretion. The greater activity of SS-28 may be due to the higher steady state levels achieved after continuous infusion as demonstrated by the present study and in dogs (Vaysse et al 1981b).…”
Section: Discussionmentioning
confidence: 74%